Pengaruh Kompensasi Eksekutif dan Gender Diversity Terhadap Tax Avoidance - Hajawiyah, Ain; Kiswanto; Suryarini, Trisni; Zhafira Nilnamuna, Afifah (Journal of Business And Entrepreneurship, 2025)
This study examines the effects of executive compensation and gender diversity on tax avoidance in Indonesian manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. Using purposive sampling, a sample of 75 companies, representing 175 units of analysis, was selected. The analysis, conducted with descriptive statistics and multiple linear regression using IBM SPSS 27.0, reveals that executive compensation has a negative and significant effect on tax avoidance. Conversely, gender diversity was found to have no effect. The study also found that profitability and firm size had a positive and significant effect on tax avoidance, whereas leverage had a negative and significant effect. This research contributes to existing literature by using a unique method to measure gender diversity—the number of female directors divided by the total number of directors—to study its influence on tax avoidance.